The Application of Practice Teaching Style to Improve Learning Outcomes of Forward Roll Floor Gymnastics in Fourth Grade Elementary School Students - Kurniawan, Panca; Sihombing, Hardodi; Keliat, Pedomanta (Educational Sciences Journal, 2025)
This study aims to determine the effectiveness of applying the practice teaching style in improving students’ learning outcomes on the forward roll movement in floor gymnastics among fourth-grade elementary school students. The research employed a Classroom Action Research (CAR) approach, conducted at SD Al-Ittihadiyah Percut, Deli Serdang Regency, during the 2022/2023 academic year, involving 29 students as subjects. Data were collected through observation and performance tests over two learning cycles. In Cycle I, 15 students (51.72%) achieved the minimum mastery criteria, with an average score of 72.70. In Cycle II, 26 students (89.65%) met the criteria, with an average score of 79.31. The results indicate a significant improvement in learning outcomes after applying the practice teaching style. This method provides students with greater responsibility and autonomy in the learning process, enhances motor skill mastery, and fosters more active and independent participation. Therefore, it can be concluded that the application of the practice teaching style effectively improves students’ learning outcomes in the forward roll floor gymnastics material for fourth-grade students at SD Al-Ittihadiyah Percut.